Microchilus dasilvae: a new species of Goodyerinae (Orchidaceae) from Southeastern Brazil - Engels, Mathias E.; Smidt, Eric C. (Phytotaxa, 2022)
We describe and illustrate a new orchid species, Microchilus dasilvae, belonging to the Goodyerinae subtribe, found in the Atlantic Forest Domain of southeastern Brazil in an ecotonal region between Dense Ombrophilous Forest and Semideciduous Seasonal Forest. The species has an affinity with Microchilus decorus and Microchilus metallescens. It differs by the lip with a trilobed, yellow mesochile with acute lateral lobes, and by the broad-ovate epichile, about the same width as the mesochile when flattened.